Legal Regulation Problems of Employment Quoting for People with Disabilities - R. N. Zhavoronkov (Сибирское юридическое обозрение, 2014)
The article deals with the definition of employment quoting, the analysis of changes in legal regulation of employment quotas for people with disabilities during the last decade, here is considered the effectiveness of employment quotas as the means of employment for people with disabilities. The directions of quoting legislation improvement are determined.